Media 1974-75 Purdue University Bulletin. - Purdue Univ., Lafayette, IN. Audio-Visual Center; Purdue Univ., Lafayette, IN. Audio-Visual Center ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
This catalog lists motion pictures, slides and media kits available from the Audio-Visual Center of Purdue University, covering a wide variety of subjects. Directions are provided for ordering these materials from the Center. Titles are listed alphabetically with citations noting media format, running time, grade level (elementary through adult), producer/vendor, rental cost and content description. Titles are also listed, by type of media, in a subject index. (SL)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Audiovisual Aids; Catalogs; College Libraries; Films; Library Collections; Slides; Purdue University IN